Purification and concentration of infectious koi herpesvirus using steric exclusion chromatography - Eilts, Friederike; Jordan, Lisa; Harsy, Yasmina M.J.; Bergmann, Sven M.; Becker, Anna; Wolff, Michael W. (Journal of Fish Diseases, 2023)
Koi herpesvirus (KHV) is the causative agent of a koi herpesvirus disease (KHVD) inducing high mortality rates in common carp and koi (Cyprinus carpio). No widespread effective vaccination strategy has been implemented yet, which is partly due to side effects of the immunized fish. In this study, we present an evaluation of the purification of infectious KHV from host cell protein and DNA, using the steric exclusion chromatography. The method is related to conventional polyethylene glycol (PEG) precipitation implemented in a chromatographic set-up and has been applied for infectious virus particle purification with high recoveries and impurity removal. Here, we achieved a yield of up to 55% of infectious KHV by using 12% PEG (molecular weight of 6 kDa) at pH 7.0. The recoveries were higher when using chromatographic cellulose membranes with 3–5 μm pores in diameter instead of 1 μm. The losses were assumed to originate from dense KHV precipitates retained on the membranes. Additionally, the use of >0.6 M NaCl was shown to inactivate infectious KHV. In summary, we propose a first step towards a purification procedure for infectious KHV with a possible implementation in fish vaccine manufacturing.<br
Keywords: cyprinid herpesvirus 3; downstream processing; fish health management; fish vaccination; vaccine manufacturing